Blockchain Technology for Business Audit in Agriculture, Review - Loredana Adriana SAGHIN (DIMA); Constanta Laura AUGUSTIN (ZUGRAVU); Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2021)
One model for understanding the blockchain is to compare it to a recording and inventory system so that the recording, tracking, monitoring and trading of all assets could be managed with the blockchain. A blockchain business audit is a database that contains the history of all exchanges made between its users, since its creation. In short, it is a digital transformation of different systems of economics, including agriculture. Agriculture is confronted with a series of challenges that will affect both our opportunities and global risks. Growth of agri-growth in the conditions of living standards, no radical changes in the agro-food sector. This study examines the potential of blоckсhаin technology in agriculture business audit. In conclusion, in some fields such as forecasting weather or agricultural expert systems are sometimes more accurate than humans.
Keywords: Blockchain; Artificial Intelligence; Agriculture.